A Study on the Mechanism of Video Games in Stimulating Tourism Intention Based on the CAC Framework - Xie, Shengsheng (Economics & Management Review, 2025)
Using the cognitive-affective-conative (CAC) framework and place attachment theory, this study examines how the video game "Black Myth: Wukong" impacts tourism motivation for Shanxi's Xiaoxitian in Xi County. Structural equation modeling reveals that gaming experiences positively influence tourism intentions through dual mediation of destination image perception (β=0.498) and place attachment (β=0.244), creating a chain mediation effect (effect size 0.146). The study shows that video games boost cultural and tourism consumption via a "cognition reinforcement emotion sedimentation behavior transformation" mechanism. It suggests destinations collaborate with the gaming industry to use digital scenes and cultural symbols to spread heritage digitally and convert it into tourism.